PENGARUH PENGGUNAAN MEDIA SOSIAL FACEBOOK TERHADAP KARAKTER PESERTA DIDIK PADA MATA PELAJARAN IPS KELAS VIII SMP MUHAMMADIYAH 1 METRO TAHUN PELAJARAN 2019/2020 - Minin Minin; Elis Setiawati; Tiara Anggia Dewi (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2021)
Facebook social media is a medium that is used to publish content, such as profiles, activities or even user opinions and also as a medium that provides space for communication and interaction in social networks in cyberspace. Facebook is in great demand by the Indonesian people, from children to adults from remote villages to city centers are familiar with Facebook. The breadth of the network created by Facebook makes its users think to take advantage of it, ranging from positive things to crime. The use of Facebook social media at this time is very diverse, as for the negative impact of Facebook social media that has occurred recently, namely a lot of news in print and electronic media regarding the misuse of Facebook social media, reporting on crimes and crimes that started from introductions on Facebook social media. . The purpose of this study was to determine the effect of using Facebook social media on the character of social studies subjects for class VIII students of SMP Muhammadiyah 1 Metro for the 2019/2020 school year. The number of samples used as many as 55 students with the determination of the sample using stratified random sampling technique. The technique of data collection was done by using a questionnaire. The data analysis technique used a simple linear regression analysis technique. Based on the results of the study, regarding the effect of social media facebook on the character of students in social studies subjects for class VIII SMP Muhammadiyah 1 Metro, it can be concluded that there is a significant influence between the use of social media facebook on the character of students in social studies subjects. In the calculation of the coefficient of determination (KD) the value of KD = 42.4% is obtained, which means: the effect of using Facebook social media on the character of students in social studies subjects is 42.4%, while 57.6% is influenced by other factors that have not been studied. is known. For the next research can expand the coverage area so that it represents the actual situation